2013
DOI: 10.2172/1183635
|View full text |Cite
|
Sign up to set email alerts
|

NDE to Manage Atmospheric SCC in Canisters for Dry Storage of Spent Fuel: An Assessment

Abstract: In this effort, an assessment of bulk ultrasonic (UT) and eddy current (ECT) methods and techniques is performed for inspecting the surfaces of dry cask storage systems (DCSSs) canisters. Some DCSS canisters (especially those located in coastal environments) will be exposed to environmental conditions, which can cause atmospheric stress corrosion cracking (SCC). Information collected from the field and from laboratory studies has not been able to rule out the possibility of atmospheric SCC in DCSS canisters, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…In the HI-STORM system, crevice conditions occur where the multipurpose canister bottom plate contacts the pedestal. In the NUHOMS system, crevice conditions occur where the dry shielded canister contacts the support rails [2].…”
Section: Introductionmentioning
confidence: 99%
“…In the HI-STORM system, crevice conditions occur where the multipurpose canister bottom plate contacts the pedestal. In the NUHOMS system, crevice conditions occur where the dry shielded canister contacts the support rails [2].…”
Section: Introductionmentioning
confidence: 99%
“…There are many cases where nondestructive inspection (NDI) of structures, such as pipelines and containers, needs to occur in harsh environments, including elevated temperature and radioactivity in the nuclear power industry. An excellent example considered in this research is dry storage casks for spent nuclear fuel, shown in Figure 1 a [ 1 , 2 , 3 , 4 , 5 ]. The dry storage cask consists of a welded austenitic stainless steel cylindrical canister that confines spent nuclear fuel and a concrete/steel overpack that shields and protects the canister.…”
Section: Introductionmentioning
confidence: 99%
“…The canister is roughly 2 m in diameter and 5 m long [ 5 ]. Chloride-induced stress corrosion cracking (SCC) in the heat affected zone (HAZ) of full penetration welds in the canister is a potential aging mechanism of the canister [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ], which should be inspected for in order to ensure the continued health and performance of the dry storage cask. However, the environment in the plenum between the canister and the overpack has both elevated temperature and gamma radiation that both gradually decrease over time in storage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Issues related to nondestructive evaluation of dry storage casks for spent nuclear fuel have been described elsewhere by the authors [1] and in numerous reports [e.g., [2][3][4][5]. Spent nuclear fuel goes to wet storage and then dry storage prior to disposal.…”
Section: Introductionmentioning
confidence: 99%